The Modifications in Physicochemical and Functional Properties of Proso Millet Starch after Ultra‐High Pressure (UHP) Process. (15th March 2018) - Li, Wenhao; Gao, Jiaxing; Saleh, Ahmed S. M.; Tian, Xiaolin; Wang, Peng; Jiang, Hao; Zhang, Guoquan
Abstract : Proso millet starch suspensions (30%, W/V) are subjected to UHP treatment at 150, 300, 450, and 600 MPa for 15 min in order to produce a modified starch for food applications. Besides, the UHP‐gelatinized starch gels are stored at room temperature for 192 h and the recrystallization characteristics are investigated during the storage time. The gelatinization extent of starch is increased with the increase in pressure level and the starch is fully gelatinized at 600 MPa. The XRD patterns show that the UHP at 600 MPa converted the A‐type crystals to the B‐type. The DSC data reveal an increase in gelatinization temperatures and a decrease in gelatinization enthalpy after treatment at 150–450 MPa. Pasting property analysis shows that trough and final viscosity, pasting temperature and peak time are increased; however, peak and breakdown viscosity are decreased with the increase in pressure level up to 600 MPa. UHP treatment resulted in a higher swelling capacity and solubility at a relatively low temperature. XRD and DSC are also used to monitor retrogradation through the growth of diffraction peaks of the recrystallized starch and the increase in the melting enthalpy. The extent of retrogradation is plotted as a function of the storage time. Abstract : The findings of this study suggested that UHP processing at pressure levels up to 600 MPa could be an alternative technique for obtaining modified starch for food industry applications. The extent of physicochemical and functional properties, and retrogradation extent of millet starch are plotted as a function of the storage time.